Interspecific potato breeding lines display differential colonization patterns and induced defense responses after Ralstonia solanacearum infection - Ferreira, Virginia (2017)
Fil: Fil: Ferreira, Virginia. Universidad de la República. Facultad de Química. Departamento de Biociencias; Uruguay.